Identifying key factors for successful development of agricultural biogas plants in Poland - Ginda, Grzegorz; Szyba, Marta (Wydawnictwa AGH, 2022)
In Poland, the potential for biogas production is high. It is an important source of renewable energy and contributes to reducing methane emissions (a greenhouse gas). In this article, the implementation of an agri-gas plant-construction program was evaluated in individual voivodeships based on materials from the National Agricultural Advisory Center (KOWR), the literature, and statistical data. Based on the collected data, it was concluded that the most meaningful factors for the successful development of Polish agricultural biogas plants were biogas-production technology, substrate availability, energy prices from renewable energy sources, waste-disposal costs, the population density in a commune, and the allocation of places in local spatial-development plans. The DEMATEL technique was used to identify the key developmental factors. The results of the study provide useful information for both governments and local authorities in their searches for effective ways to drive the sector’s development.
Decision Making in Manufacturing and Services
Keywords: agricultural biogas plants; development; factor; identification; pairwise comparison; DEMATEL